Effect of Alcohol-Patterns in the Resiliency of South Korean Firefighters from Job Stress and Incident Impact - Cha, Jingyung; Park, Chanseok; Bang, Seonghwan; Cho, Byungjun (International Journal of Engineering and Technology, 2019)
In The purpose of this study is to improve the safety and work efficiency of firefighters by exploring how resilience contributes to the relationship and to provide basic data for the management program of traumatic stress. With the help of the fire department, we collected data through a self - report questionnaire consisting of self - report scale for 300 public officials. Data collection methods were based on e-mail sending and returning methods, There were 270 subjects in the analysis except for 30 subjects who were not or not reliable.Normal drinking group showed mediating effect of resiliency(p <.001). The higher the stress (B = -0.700, B is a regression coefficient ), the lower the resilience(B = -12.338) and the lower the event impact. The indirect effect of stress on event impact is 8.637.The risk drinking group showed a mediating effect of resilience (p <.001). The higher the stress (B = -0.729), the lower the resilience (B = -12.853) and the lower the event impact.The indirect effect of stress on event impact is 9.370. (P> .05). The estimated alcohol use disability group showed no mediating effect of resilience. This suggests that strengthening resilience may contribute to the management of post-traumatic stress. On the other hand, in the case of the alcohol-use disability, a therapeutic approach from the viewpoint of more fundamental substance addiction is necessary.Â Â